The Drosophila embryonic patterning determinant torsolike is a component of the eggshell. - Stevens, L.M.; Beuchle, D.; Jurcsak, J.; Tong, X.; Stein, D. (Current Biology, 2003)
The development of the head and tail regions of the Drosophila embryo is dependent upon the localized polar activation of Torso (Tor), a receptor tyrosine kinase that is uniformly distributed in the membrane of the developing embryo. Trunk (Trk), the proposed ligand for Tor, is secreted as an inactive precursor into the perivitelline fluid that lies between the embryonic membrane and the vitelline membrane (VM), the inner layer of the eggshell. The spatial regulation of Trk processing is thought to be mediated by the secreted product of the torsolike (tsl) gene, which is expressed during oogenesis by a specialized population of follicle cells present at the two ends of the oocyte. We show here that Tsl protein is specifically localized to the polar regions of the VM in laid eggs. We further demonstrate that although Tsl can associate with nonpolar regions of the VM, the activity of polar-localized Tsl is enhanced, suggesting the existence of another spatially restricted factor acting in this pathway. The incorporation of Tsl into the VM provides a mechanism for the transfer of spatial information from the follicle cells to the developing embryo. To our knowledge, Tsl represents the first example of an embryonic patterning determinant that is a component of the eggshell.